Lead induced Morphological Changes in the Kidneys of Albino Mice - Bilquis Begum٭, IramNadeemRana , MudassarMajeed (Journal of Rawalpindi Medical College, 2014)
Background: To find out the morphological effects of different doses of lead acetate on the kidneys of mice at different intervals of time. Methods: A total of 72 albino mice were taken, after acclimatization. They were grouped in 4 groups, A, B, C and D, each having 18 mice. Groups B, C and D received lead acetate in deionized water in the doses of 2, 4 and 8 mg / kg / day respectively, while group A received only deionized water.After every 3 weeks, 6 animals from each group were sacrificed and kidneys were processed for histopathological examination. Their morphology was seen and findings were compared with control groups. Results: Initial lesions observed at 3 weeks duration were cytomegaly and karyomegaly of lining epithelium of proximal tubules along with hydropic change. At this stage glomeruli showed congestion, prominent lobulation and increased cellularity. Interstitium showed mononuclear infiltration.These changes were followed at higher levels and duration of exposure by tubular dilatation, basement membrane thickening, tubular necrosis and Intraluminal casts along with signs of regeneration (binuclear cells in tubular lining), vessel walls thickening, interstitial mononuclear infiltration and fibrosis. Conclusion: Kidney is a sensitive organs to chronic low level lead toxicity causing permanent damage, which can ultimately lead to renal failure. The effects are dose and duration dependent.